Clinical Research Nurse involvement to foster a community based transcultural research in RODAM European study - Caselgrandi, Agnese; Guaraldi, Giovanni; Cottafavi, Katiuscia; Artioli, Giovanna; Ferri, Paola (Acta Biomedica Atenei Parmensis, 2016)
Background and aim of the work: The Clinical Research Nurse (CRN) can be considered the fulcrum of clinical studies, being a vital link between patient, principal investigator, study sponsor and administrative staff. The clinical research’s way is still long and the contribution that CRNs can provide is crucial. In Italy, a CRN was employed in the study: Research on Obesity & Type 2 Diabetes among African Migrants (RODAM). The aim of the paper is to explore and describe the experience of this involvement. Methods: The CRN managed the project in order to gain a complete collaboration from the Ghanaian population. From the first contact, the CRN decided to adopt a transcultural approach with the aim to create a relationship of understanding, mutual trust respect for each other’s cultural diversity. The CRN also used organizational, technical and linguistic skills. Results: The day-to-day trial management from CRN included the following activities: obtaining local Ethics Committee study approval; recruiting the study staff; planning the study activities; identifying potential study participants; collaborating with the mediators; managing contacts with other RODAM centers; conducting a follow-up of patients. The most important results of CRN involvement have been the empowerment of Ghanaian community and the effective healthcare promotion. Conclusions: The project encouraged the Ghanaian community to increase their healthcare awareness and encouraged the Ghanaian population to create new strategies to face the hard health challenges.